Electronic properties of Zintl phase hydride for hydrogen storage - K. Khodja; Y. Bouhadda (Revue des Énergies Renouvelables, 2014)
In this paper we report the SrAl2H2 electronic properties which is a Zintl phase hydride in frame of the Density Functional Theory ‘DFT’ using the plane wave and pseudo potential method. We discuss the chemical bond nature using total and partial density of states ‘DOS and PDOS’, also we calculated the bonding distance of hydride compound and its precursor SrAl2 and the enthalpy formation of the SrAl2H2 for hydrogen storage.